Superficial radiotherapy as a treatment alternative for recurrent conjunctival squamous cell carcinoma: a case study. Issue 3 (25th March 2018) - Edgar, Amanda; Crutchfield, Gretel; Anderson, Nigel
Abstract: This case study discusses the use of superficial radiotherapy (SXRT) in the treatment of recurrent conjunctival squamous cell carcinoma (SCC). Conjunctival SCC is often an aggressive cancer, with surgery the current standard of care. There is currently limited literature on alternative treatment options to treat conjunctival SCC recurrences that enable ocular function preservation. Furthermore, the use of SXRT in this setting is not well‐reported. Technical feasibility, practical limitations and potential side effects of SXRT (in comparison to other treatment options) are discussed in this case study. This case describes a 62 years old male with limited treatment options following multiple recurrences of conjunctival SCC. He was prescribed a therapeutic SXRT dose of 48.4 Gy in 22 fractions (5 fractions/week). At 6‐month follow‐up, there was no evidence of residual or recurrent disease, or any significant objective or patient reported treatment induced side effects. This case study provides preliminary evidence for the potential application of SXRT for conjunctival SCC. The benefits reported in this case study warrant further investigation of the applicability of SXRT in a larger patient cohort, with the potential to provide patients with a less invasive treatment alternative for recurrent conjunctival SCC. Abstract : This case study presents an alternative approach to traditional treatments for recurrent conjunctival squamous cell carcinoma. There is currently little consensus in the literature as the optimal care pathway for patients presenting with this condition. In this case, superficial radiotherapy provided an efficient, less invasive, less morbid and cosmetically improved patient alternative.